Development of Mathematics Learning Tools In The New Normal Era for MTs Students to Practice Critical Thinking - Eko Yuniarto; Nia Wahyu Damayanti; Umul Khayati (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
The purpose of this research is that learning in Indonesia continues. The Covid-19 pandemic in Indonesia has made learning carried out online. Therefore, Learning Tool Development is also carried out online by utilizing E-Learning. The e-Learning used is zoom, quizizz, and google classroom. With online learning, it is hoped that students will remain enthusiastic in carrying out learning, even though there are many obstacles experienced by students during this online learning. Learning tools provided online are expected to train students' critical thinking in ways or strategies to solve mathematical problems or problems. By designing learning tools that are attractive, creative, and efficient so that students do not get bored during online learning, and can use smartphones positively and wisely. Learning kits consist of lesson plans, quizizz-based worksheets, and YouTube audio-visual materials. The purpose of this research is for learning to continue even in the new normal era due to the Covid-19 pandemic, by utilizing technology and information media such as E-learning.